ABOUT THE CHARMING CREATION OF ZEBU UN-NISSA BEGIM - Bekmirzaev Rakhmonali Begalievich; Akhmatova Ainura Nimatovna (Academia Science Repository, 2023)
This article is devoted to the problems of the source and time, which influenced the formation of personality under the conditions of feudal oppression, reinforced by religious dogmatism. The article also mentions the work of Zebu un -nissa begum, one of the Timurid poets, who was born into an aristocratic family and received an excellent education and upbringing, which prompted him to think and believe in a better future in the most difficult moments of his life.